2013
DOI: 10.1017/s1461145713001545
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of alcohol drinking in mice depends on alterations in RNA editing of serotonin 2C receptors

Abstract: Serotonin 2C receptors (5-HT2CR) are G-protein-coupled receptors with various actions, including involvement in drug addiction. 5-HT2CR undergoes mRNA editing, converting genomically encoded adenosine residues to inosines via adenosine deaminases acting on RNA (ADARs). Here we show that enhanced alcohol drinking behaviour in mice is associated with the degree of 5-HT2CR mRNA editing in the nucleus accumbens and dorsal raphe nuceus, brain regions important for reward and addiction. Following chronic alcohol vap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…Two-way ANOVA analysis showed a significant difference in receptor activity (isoform: F 1,40 =80.26, p<0.01; 5-HT treatment: F 3,40 =21.66 p<0.01; isoform×5-HT: F 3,40 =3.01, p<0.05). This isoform difference has previously been reported in various studies (Burns et al 1997;Fitzgerald et al 1999;Wang et al 2000;Gurevich et al 2002a;Watanabe et al 2014); therefore, our results demonstrate correct functioning of the 5-HT 2C R-Tango system.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Two-way ANOVA analysis showed a significant difference in receptor activity (isoform: F 1,40 =80.26, p<0.01; 5-HT treatment: F 3,40 =21.66 p<0.01; isoform×5-HT: F 3,40 =3.01, p<0.05). This isoform difference has previously been reported in various studies (Burns et al 1997;Fitzgerald et al 1999;Wang et al 2000;Gurevich et al 2002a;Watanabe et al 2014); therefore, our results demonstrate correct functioning of the 5-HT 2C R-Tango system.…”
Section: Resultssupporting
confidence: 90%
“…editing of 5-HT 2C R mRNA may have causative relevance to neuropsychiatric disorders (Maas et al 2006;Iwamoto et al 2009). Moreover, we recently demonstrated that after long-term alcohol exposure, alterations in 5-HT 2C R RNA editing are involved in alcohol preference (Yoshimoto et al 2012;Watanabe et al 2014). Overall, these findings indicate that modulation of 5-HT 2C R activity is involved in various brain functions.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Stimulation of the 5-HT2CR is also suppressing ethanol self-administration (Maurel et al 1999;Tomkins et al 2002;Kasper et al 2013;Rezvani et al 2014) and reinstatement in rodents (Kasper et al 2013). Further, ethanol vapor exposure leads to an increased corticostriatal and hypothalamic 5-HT 2C R mRNA, increased 5-HT 2C R protein in the NAc and 5-HT2CR pre-mRNA editing (Yoshimoto et al 2012;Watanabe et al 2014). The behavioral effects of d-amphetamine (O'Neill et al 1999;Rippberger et al 2015;Wohr et al 2015), 3,4-methylenedioxymethamphetamine (MDMA) (Bankson and Cunningham 2002;Fletcher et al 2002b), methamphetamine (Steed et al 2011;Graves and Napier 2012), and the marijuana alkaloid 9 -THC (Ji et al 2006) can be modulated by the administration of 5-HT2CR agonists, thus extending the potential therapeutic value of selective 5-HT2CR agonists in the treatment of substance abuse.…”
Section: Addiction and Substance Use Disorders: Lorcaserinmentioning
confidence: 99%